PENGEMBANGAN INSTRUMEN TES BERBASIS MULTIREPRESENTASI PADA MATA KULIAH PENDAHULUAN FISIKA ZAT PADAT - Lusi Rizki Aulia; ismet ismet; zulherman zulherman (Universitas Sriwijaya, 2016)
Has successfully developed multiple representation based a test instrument in the subject of Introduction to Solid State Physics who was valid, practical, and reliable. The development of test instrument was using a researh development, type of formative research, who was decided by the needs of the research. In the preliminary stage, orientation and initial prototype was conducted. In the prototyping stage, Tessmer evaluation was done to evalute initial prototype. The evaluations includes self-evaluation, expert review, one-to-one evaluation, and small group evaluation. The research instrument were used validation sheets and questionnaires. The results of expert reviews indicate that the test instrument developed classified as very valid (0.91). The results of one-to-one and small group evaluation indicates that the test instrument developed relatively practical. At the stage of one-to-one evaluation, gained an average 3.16 from the recapitulation of questionnaire (practically category). At the stage of small group evaluation, gained an average 3.26 from the recapitulation of questionnaire (practically category). All of matter who was tested meet the criteria for a reliable where r11> rtable. Thus, based on the results showed that the developed test instrument has been classified as very valid, practical, and reliable so that it can be used in the course of Introduction to Solid State Physics.